Exploration of Bacillus thuringiensis ä-Endotoxin Derived from Bacterial Isolates in Jabodetabek Region - EDDY JUSUF (Microbiology Indonesia, 2009)
Bacillus thuringiensis is a well-known species of bacteria producing parasporal crystalline proteins that are toxic to many insect pests, it also has strong cytocidal activity against human cancer cells. In this work we endeavoured to explore the city of Jakarta and its neighbouring regencies to obtain new strains to profile its potency. The soil samples were boiled and plated on T-3 agar; the colonies which appeared were then examined under the light microscope to check for crystalline proteins. The proteins were treated with 1% SDS-0.01% b-mercaptoethanol and visualized by SDS-PAGE to determine their molecular size. From 52 soil samples, 1248 putative colonies were obtained. After microscopic examination, 57 isolates showed the existence of crystalliferous protein, of those 30 indicated many sizes of ä-endotoxin protein from approximatively 150 kDa to the smallest 35 kDa. Most of proteins examined probably showed insecticidal activity and four of those were predicted to possess cytocidal activity against human cancer cells. The geographic condition did not appear to influence the distribution of different types of äendotoxin.